In Principio - Martello, Ruben (Brepols, 2025)
This volume offers a fresh approach to the structure of Bonaventure’s thought. Ruben Martello argues that Bonaventure employs the Genesis creation account as an overarching framework and fecund source for understanding nature, theology, and even Scripture itself. Beginning with Bonaventure’s view of the literal meaning of Scripture, the reception of the hexaëmeron is traced chronologically in a number of major theological works. Bonaventure is interpreted in light of the hexameral commentarial tradition like Augustine’s <span class=